2013
DOI: 10.1590/s0103-05822013000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação clínica e evolutiva de crianças em programa de atendimento ao uso de fórmulas para alergia à proteína do leite de vaca

Abstract: Digestive manifestations of cow's milk allergy were preponderant, and lead to greater nutritional impairment. The use of replacement formulas (isolated soy protein and protein hydrolysates) was important to maintain the nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
1
5
0
6
Order By: Relevance
“…Aguiar et al, in a descriptive study at Rio Grande do Norte, Brazil, using similar methodology to the one employed in the present study, evaluated 214 children diagnosed with CMPA, referred to the Program of formulas for cow´s milk allergy at in a Pediatric University hospital, the mean age was 3 months and they found that 49.5% of patients with clinical manifestations presented impairment of the digestive system simultaneously with other systems, such as respiratory and the skin. In the same study, they found 34.6% of patients with allergic colitis and the nutritional status analyzed by ZBMI showed thinness at 12.9%, 67.8% in normal weight, overweight risk in 15.2% and overweight at 4.1% (2) . In accordance to the presented by the review study, we did not find statistically significant differences in relation to nutritional status before and after nutritional intervention when analyzing the parameters only.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Aguiar et al, in a descriptive study at Rio Grande do Norte, Brazil, using similar methodology to the one employed in the present study, evaluated 214 children diagnosed with CMPA, referred to the Program of formulas for cow´s milk allergy at in a Pediatric University hospital, the mean age was 3 months and they found that 49.5% of patients with clinical manifestations presented impairment of the digestive system simultaneously with other systems, such as respiratory and the skin. In the same study, they found 34.6% of patients with allergic colitis and the nutritional status analyzed by ZBMI showed thinness at 12.9%, 67.8% in normal weight, overweight risk in 15.2% and overweight at 4.1% (2) . In accordance to the presented by the review study, we did not find statistically significant differences in relation to nutritional status before and after nutritional intervention when analyzing the parameters only.…”
Section: Discussionmentioning
confidence: 74%
“…In this study, 70% of the patients were eutrophic and 30% was malnourished, however, the nutritional parameters were measured using the Gomez criteria (11) . It is important to consider that studies which demonstrate the effects of nutritional therapy in the development of infants with AP has emphasized the use of hydrolyzed formulas, soy-based formulas and exclusion diets as forms of treatment (2,11,16) . Yonamine et al in a literature review, reports a study carried out with 168 infants with CMA evaluating nutritional status, which were assigned to two groups, namely: one received soy-based formula and the other received extensively hydrolysed formula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Alergia Alimentar (AA) se refere a uma resposta imunológica anômala, que ocorre após a ingestão ou contato com determinados alimentos 1 . Dentre os alérgenos alimentares, a proteína do leite de vaca é considerada o mais frequente componente dietético causador de alergia 2 . Na alergia ao Leite de Vaca (ALV) ocorre uma reação imune contra algumas proteínas presentes no leite de vaca, principalmente a beta-lactoglobulina, alfalactoalbumina e a caseína…”
Section: Introducãounclassified
“…qualidade nutricional e importante fonte de cálcio, fósforo e aminoácidos essenciais(AFFINITTA et al, 2013;BONJOUR et al, 2013). Mas atualmente existe uma tendência de substituição desses alimentos devido ao fato de a proteína do leite de vaca ser o mais frequente componente causador de alergias alimentares(AGUIAR et al, 2013). avaliar o efeito da ingestão de maiores níveis de cálcio na dieta sobre o risco de desenvolvimento de câncer colorretal.…”
unclassified